No Association between Daily Walking and Knee Structural Changes in People at Risk of or with Mild Knee Osteoarthritis. Prospective Data from the Multicenter Osteoarthritis Study - Oiestad, Britt Elin; Quinn, Emily; White, Daniel; Roemer, Frank; Guermazi, Ali; Nevitt, Michael; Segal, Neil A.; Lewis, Cora E.; Felson, David T. (Journal of Rheumatology, 2015)
We investigated the association between objectively measured daily walking and knee structural change, defined either as radiographic worsening or as cartilage loss, in people at risk of or with knee osteoarthritis (OA).Participants from the Multicenter Osteoarthritis Study (MOST) with Kellgren-Lawrence grades 0-2 and daily walking (measured with the StepWatch) at the 60-month visit were included. Participants had fixed-flexion, weight-bearing radiographs and knee magnetic resonance images (MRI) at 60 and 84 months. Radiographic worsening was read in both knees using the Osteoarthritis Research Society International grading, and MRI were read for 1 knee using the Whole-Organ MRI Score semiquantitative scoring. OR and 95% CI were calculated comparing those in the middle tertile against the lowest and highest tertiles of daily walking using logistic regression models and generalized estimating equations. Data on walking with moderate to vigorous intensity (min with > 100 steps/min/day) were associated to structural change using multivariate and logistic regression models.The 1179 study participants (59% women) were 67.0 years old (± 7.6), with a mean (± SD) body mass index of 29.8 kg/m(2) (± 5.3) who walked 6981 (± 2630) steps/day. After adjusting for confounders, we found no significant associations between daily walking and radiographic worsening or cartilage loss. More time spent walking at a moderate to vigorous intensity was not associated with either radiographic worsening or cartilage loss.Results from the MOST study indicated no association between daily walking and structural changes over 2 years in the knees of people at risk of or with mild knee OA.
EVALuna2:14537